A state-of-the-art review and analysis on the design of dry adhesion materials for applications such as climbing micro-robots. Issue 63 (10th July 2015) - Sahay, Rahul; Low, Hong Yee; Baji, Avinash; Foong, Shaohui; Wood, Kristin L.
<x xml:space="preserve">Abstract</x> This article highlights the design considerations for the development of robust and durable bio-inspired synthetic adhesives.